2023
DOI: 10.1098/rsob.230217
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular signatures of motherhood in the adult and ageing rat brain

P. Duarte-Guterman,
J. E. Richard,
S. E. Lieblich
et al.

Abstract: Pregnancy is marked by robust changes, including brain changes to volume, structure, connectivity and neuroplasticity. Although some brain changes are restricted to pregnancy and the postpartum, others are long-lasting. Few studies have examined possible mechanisms of these changes or the effects of multiple pregnancies. We characterized various cellular and molecular signatures of parity (nulliparous, primiparous, biparous) in the rat hippocampus. We investigated density of neural stems cells (Sox2), microgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
1
4
0
Order By: Relevance
“…Our results demonstrate not only that previous pregnancy, and the age of first pregnancy, can affect multiple brain parameters, but also that the effects of estradiol in middle age can vary with previous reproductive experience. This work converges with others to indicate that parity, and associated factors such as the number of pregnancies affect the trajectory of brain aging and health (Duarte-Guterman et al, 2019, 2023; Galea et al, 2018; Puri et al, 2023). With an aging global population, our work suggests that parity, and the age of first pregnancy should be taken into consideration when investigating the effects of estrogens in middle and older age.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our results demonstrate not only that previous pregnancy, and the age of first pregnancy, can affect multiple brain parameters, but also that the effects of estradiol in middle age can vary with previous reproductive experience. This work converges with others to indicate that parity, and associated factors such as the number of pregnancies affect the trajectory of brain aging and health (Duarte-Guterman et al, 2019, 2023; Galea et al, 2018; Puri et al, 2023). With an aging global population, our work suggests that parity, and the age of first pregnancy should be taken into consideration when investigating the effects of estrogens in middle and older age.…”
Section: Discussionsupporting
confidence: 87%
“…These cytokines are 'antiinflammatory' and have very closely linked functions, and are secreted by Th2 type T-cells (KleinJan et al, 1999;Yssel & Groux, 2000). Although there are some previous studies that have investigated the effects of parity and inflammation and found no effect of parity on IL-13, IL-10, or TNF-α, they did not consider any hormonal treatment or age of first pregnancy, and also looked at circulating cytokines, whereas our study investigated cytokine levels in brain tissue (Duarte-Guterman et al, 2023;Eid et al, 2019).…”
Section: An Older Age Of First Pregnancy Increases Hippocampal Neurog...mentioning
confidence: 97%
See 2 more Smart Citations
“…For each marker, counts were average from four dorsal and three ventral sections per individual. In addition, Iba-1 morphology was categorized into three groups: ameboid, stout/thick, and thick/thin, similar to previous work (Duarte-Guterman et al, 2023; Eid et al, 2019). Categorization was based on the branching of the processes, with an ameboid morphology having no processes, a stout/thick morphology having one to two processes close to the cell body, and a thick/thin morphology having several thin processes extending outwards from the cell body (Figure 1B-D).…”
Section: Methodsmentioning
confidence: 90%